Dual function of mitochondrial complex III in Plasmodium falciparum - River S. Rell; Anurag Shukla; Joanne M. Morrisey; Ijeoma C. Okoye; Michael W. Mather; Akhil B. Vaidya (PLoS ONE, 2026)
Complex III of the malaria parasite mitochondrial electron transport chain (mtETC) has been validated as an attractive target for currently used antimalarials. We previously showed that the main function of mtETC in blood stage Plasmodium falciparum is to regenerate ubiquinone, which serves as an obligatory co-substrate of dihydroorotate dehydrogenase (DHOD), an essential mitochondrial enzyme for pyrimidine biosynthesis. P. falciparum can be rendered resistant to all mtETC inhibitors by provision of a bypass mediated by cytosolic yeast DHOD, a fumarate-reducing enzyme. Malaria parasite mitochondrial DNA (mtDNA) encodes only 3 proteins, each a component of mtETC. However, attempts to eliminate mtDNA in transgenic parasites expressing yDHOD have been unsuccessful, suggesting the possibility that essential function(s) other than the canonical redox reactions of the mtETC also require mtDNA maintenance. Here we have tested the hypothesis that Complex III serves the dual functions of processing imported mitochondrial proteins, as well as ubiquinone regeneration. We have generated transgenic lines that conditionally express mitochondrial processing peptidase a (MPPα), which is also a component of Complex III. Using these parasites, we have determined that MPPα is essential even when the need for mitochondrial electron transport is bypassed. MPPα knockdown also resulted in hypersensitivity of the parasites to proguanil, a drug that synergizes with mtETC inhibitors such as atovaquone. Pulldown with MPPα followed by proteomics revealed the association of multiple mitochondrially targeted proteins, in addition to all components of Complex III. These results are consistent with the suggestion that Complex III in P. falciparum serves both mtETC and protein processing functions in mitochondrial physiology.